(حركية المصطلح السيميائي) في ظل الترجمة المتخصصة: Kinetics of the semiotic term under specialized translation - berkani , Hayet (Maalim, 2023)
Scientific simplification is one of the most important processes that are concerned with topics directed to non-specialists. This is achieved by adopting terms with precise and accurate concepts, which can only be accessed through reviewing the most basic principles, scientific discoveries, and technical research. since translation is the method concerned by the science of signs, (semiology) this caused a terrible acceleration of the emergence of many terms on the level of the critical arena, what is known as the semiotic term appeared within the ancient literature with the word (chemistry), which is a science closer to magic. The science of semiotics is a term that has sparked great controversy over its concept because of the multiplicity of opinions and theories about it and the inability to determine the identity of this type of knowledge in the community and because the term is translated. This is what the research aims to study trying to answer the following questions, did translation affect this science as a western translated term? How was it applied to the texts as a procedural method? And what is the impact of these translated texts on the receiver